Evaluation agronomique de trois espèces de Egusi (Cucurbitaceae) utilisées dans l’alimentation au Bénin et élaboration d’un modèle de prédiction du rendement. - Achigan-Dako, Enoch Gbenato; FANOU, N.; KOUKE, A.; Avohou, Hermane T.; VODOUHE, RAYMOND; AHANCHEDE, ADAM (My University, 2006)
Agronomic evaluation for three Egusi species (Cucurbitaceae) used as food in Benin and model analysis for yield prediction. Six varieties of Egusi from three species of cucurbit were evaluated for the fruit and the seed yield at the Agricultural Research Centre of Niaouli (South-Benin). Using randomised blocs, the agronomic characters such as the germination percentage, the fl owering date, the number of fruit per plant, the average fruit weight, the weight of 1,000 unhulled seed, the weight of 1,000 hulled seed, the ratio kernel/seed, the fruit yield, the unhulled seed yield and the hulled seed yield (kg.ha-1)were measured. Out of the six varieties, Aklamkpa (Lagenaria siceraria) showed the highest yield for dehulled and unhulled seed. It is followed by Kilonon and Kakoun (Citrullus lanatus) which yielded more than 200 kg.ha-1. In contrary Zohan (Cucumeropsis edulis), well appreciated by consumers for its organoleptic qualities, appeared to have the lowest yield in addition to the fact that it is a late variety. The prediction model analysis indicated that the number of fruits per plant and the average fruit weight are good estimators of the unhulled and hulled seed yield and could effectively contribute to the increase of seed yield in egusi crops. © 2006, FAC UNIV SCIENCES AGRONOMIQUES GEMBLOUX. All rights reserved. Agronomic evaluation for three Egusi species (Cucurbitaceae) used as food in... | Request PDF. Available from: https://www.researchgate.net/publication/290287761_Agronomic_evaluation_for_three_Egusi_species_Cucurbitaceae_used_as_food_in_Benin_and_model_analysis_for_yield_prediction [accessed Mar 20 2018].